Several international institutions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
working on tropical agriculture plan to start using CD-ROM technology in the near future. CABI has already developed a prototype containing 220,000 bibliographic abstracts that can be directly accessed by an IBM or DEC computer. The FAO has also...